PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA PADA MATERI LINGKARAN DI KELAS VIII MTS S MIFTAHUSSALAM MEDAN TAHUN PELAJARAN 2015/2016 - Desi Ratna Sari (State Islamic University of North Sumatra, 2016)
The problem in this study is less the maximum result of students'mathematics learning in class VIII-3 MTs Miftahussalam Medan. Thisis evident from the test results pre-action, observation and interviewresearchers who demonstrate a lack of understanding of the students tolearn math so that the necessary efforts and modeles teachers uselearning modeles. This study aims to increase the students' mathematicslearning in class VIII-3 MTs Miftahussalam Medan using cooperativelearning model Student Team Achievement Divisions (STAD). Thisclassroom action research conducted through two cycles that includesplanning, implementation, observation and reflection. To know theresults of students' mathematics learning, the researchers used the testresults to learn math student individually. That is the subject of thisresearch is class VIII-3 MTs Miftahussalam Terrain totaling 40 studentsconsisting of 19 male students and 21 female students. Beforeadministering the actions, the percentage of classical completeness ofthe test scores of students seen pre-action on previous material stillrelevant and classical completeness of students obtained 15% (6students) with an average of 25.625. After administering the act ofteaching through cooperative learning model Student TeamAchievement Divisions (STAD), the test results of students'mathematics learning in the first cycle, the percentage of classicalcompleteness acquired 60.00% (24 students) with an average of 65.125.Meanwhile, after repairs from the first cycle to the second cycle, the testmath achievement test in the second cycle, the percentage of classicalcompleteness acquired 87.50% (35 students) with an average grade79.625. So from the condition before being given corrective action untilthe cycle is obtained an increase of 72.5%. From the results of this classaction, the researchers concluded their mathematics learning outcomeof students with cooperative learning model Student TeamAchievement Divisions (STAD) in the class VIII-3 MTs MiftahussalamMedan.